Luxury tourism: where we go from now? - Japutra, A.; Loureiro, S. M. C.; Li, T.; Bilro, R. G.; Han, H. (Asia Pacific Journal of Tourism Research, 2022)
This research conducted a systematic review of articles on luxury consumption in tourism, specifically, its conceptualization, pre-consumption influential factors, and post-consumption responses. This paper provided an overview of relevant studies, developed a comprehensive framework, and suggested future research avenues. The present review identified that luxury consumption in tourism can be conceptualized into four different areas, which were synthesized into a cohesive framework about its creation, development, and outcome. Then, the present review identified opportunities for future research to build upon, which are breaking the stereotype, improving the “new luxury” research avenue, and developing a more comprehensive framework of luxury tourism.